The WORK THE "PANGIKET" DANCE AS A VISUALIZATION OF THE MEANING OF YELLOW FOOD IN TAKIR PLONTHANG THROUGH A DRAMATIC DANCE TYPE : 1. INTRODUCTION, 2. METHOD, 3. RESULT AND DISCUSSION, 4. CONCLUSION, 5. REDERENCE - Cahyono, Danu Soleh; Yanuartuti, Setyo (Solah, 2025)
Abstrack: The Pangiket dance work is a dance work that visualizes the meaning of yellow coconut leaves as human self-control. This dance work is based on the Ngetung Batih tradition in Dongko District, Trenggalek Regency, where this tradition is a traditional ritual to welcome the month of Suro which is full of spiritual, social, and moral meanings. One of the important elements in this ritual is the takir plonthang with yellow coconut leaves as a binder, which is interpreted as a symbol of human self-control. This meaning became the inspiration for the creation of the Pangiket dance work. The choreographic concept departs from the urgency of the value of self-control which is increasingly neglected in the younger generation amidst the rise of negative behavior. The process of creating this dance work uses Jacqueline Smith’s construction method 1 through the stages of initial stimulation, exploration, improvisation, evaluation, selection, and refinement. The form of presentation combines dramatic style with representative and symbolic modes. Other supporting elements such as costume and makeup take inspiration from Javanese aesthetics. Furthermore, this dance work is performed on a proscenium stage using various lighting systems, such as 64-par, LED par, and Fresnel. The Pangiket dance work is expected to be both a spectacle and a guide, with the main message being the importance of self-control, balance, and community, and to achieve harmony and happiness in life. Keywords: Pangiket, Yellow Leaf, Self-control, Dramatic